Signifier and Signified Meaning In "The Spongebob Squarepants Movie": A Study of Semiotics - Fauzan, Muhammad; Suswanto, Deni; Sakinah, R. Myrna Nur (Barista : Jurnal Kajian Bahasa dan Pariwisata, 2023)
Abstract In this study, the researcher analyzes the semiotics study of a movie entitled The SpongeBob SquarePants Movie, in which the movie has markers that can be used for this method. The research method chosen by the author is qualitative. The data analysis that has been chosen by the author is The SpongeBob SquarePants Movie; used as the object of analysis. To analyze the study of semiotics, the researcher decided to choose the theory of Ferdinand de Saussure, the theory of semiotics related to signifier- signified. With Ferdinand de Saussure's theory, the researcher finds scenes that contain the Semiotics of the signifier-signified in them. In the movie, the researcher can analyze Ferdinand de Saussure's theory of Semiotics visually. In addition, the researcher can find the Ferdinand de Saussure’s semiotics only 7 scenes.